Comments on 'An improved authentication scheme for mobile satellite communication systems'. (2017) - Yan, Lili; Chang, Yan; Zhang, Shibin
Recently, Lee et al. (2012) proposed an authentication scheme for satellite communication systems. Then Zhang et al. (2015) found that their scheme is vulnerable to smart card loss attack, denial of service attack and replay attack. In addition, they proposed an improved authentication scheme for satellite communication systems, and claimed resistance against these attacks. Nevertheless, in this paper, we show that the Zhang et al.'s (2015) scheme is as insecure as the original protocol against the denial of service attack. Then an improved version is proposed to avoid this security flaw. Finally, the security, reliability and performance analysis of the improved protocol are given. It demonstrates that the improved version meets the security requirements and has lower computation costs, which is more suitable for mobile satellite communication systems.